2020
DOI: 10.1007/s10943-020-01035-2
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Health and Well-Being by Putting Faith into Action During the COVID-19 Pandemic

Abstract: Anxiety and fear adversely affect the physiological systems that protect individuals from infection. This article comments on the role that religious faith and practice can play in helping individuals remain free from infection by the coronavirus and in helping to moderate the effects of infection if that should occur. The author provides six recommendations to help individuals maintain spiritual, mental, and physical resilience during these anxious times of the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
129
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 44 publications
14
129
0
6
Order By: Relevance
“…Our findings corroborate with the opinion of previous authors that R/S seems to have an important role in reducing suffering, influencing health outcomes and minimizing the consequences of social distance ( Hart, 2020 ; Hart & Koenig, 2020 ; Koenig, 2020 ). This data confirms the importance of public health measures to ensure the continuity of religious and spiritual activities during the pandemic and the training of healthcare professionals to address spiritual and religious beliefs of patients and families.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings corroborate with the opinion of previous authors that R/S seems to have an important role in reducing suffering, influencing health outcomes and minimizing the consequences of social distance ( Hart, 2020 ; Hart & Koenig, 2020 ; Koenig, 2020 ). This data confirms the importance of public health measures to ensure the continuity of religious and spiritual activities during the pandemic and the training of healthcare professionals to address spiritual and religious beliefs of patients and families.…”
Section: Resultssupporting
confidence: 92%
“…According to Koenig ( Koenig, 2020 ), social distance is an opportunity to develop a stronger relationship with God by personal religious activities, reading Holy scriptures and listening to or watching inspiring radio, podcast or TV programs. In the present study, it was possible to verify that at least one third of the participants reported having increased their religious activities during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a potential effect of religious involvement on immunity cannot be ruled out. Religious involvement may be associated with enhanced immune function, which could potentially improve resistance to viral infections (Koenig, 2020). However, such an effect has not been directly demonstrated for infections with respiratory viruses such as SARS-nCoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity has also been associated with prosocial or altruistic behaviour, which is the tendency to behave in a way that bene ts others even at a personal cost (Norenzayan & Shariff, 2008). Such behaviour may be of direct relevance in mitigating the personal and social impact of disease outbreaks (Koenig, 2020).…”
Section: Introductionmentioning
confidence: 99%